1974
DOI: 10.1084/jem.140.3.779
|View full text |Cite
|
Sign up to set email alerts
|

EVIDENCE FOR IDENTITY OR CLOSE ASSOCIATION OF THE Fc RECEPTOR OF B LYMPHOCYTES AND ALLOANTIGENS DETERMINED BY THE Ir REGION OF THE H-2 COMPLEX

Abstract: Immunoglobulin complexes, composed of heat-aggregated human Ig, were shown to bind to mouse B lymphocytes of a variety of strains, but not to either thymocytes or thymus-derived (T) lymphocytes under a variety of conditions. It was shown that this binding was not due to either natural human antibodies against mouse nor to nonspecific binding of human Ig by mouse lymphocytes. Such complexes were shown to bind to the same sites which bind mouse antibody-antigen complexes. This site is known as the Fc receptor. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
95
3

Year Published

1975
1975
2000
2000

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(112 citation statements)
references
References 39 publications
14
95
3
Order By: Relevance
“…This finding, of practical importance in interpreting results obtained with cells of various haplotype combinations, could be due to decreased efficiency of antibody binding when antigen density is reduced or to a degree of heterogeneity of gene expression among individual F~ cells. These findings differ from those obtained in the mouse, using the technique of inhibition of aggregated IgG binding by anti-Ia antisera (16), in which maximal inhibition occurred with both parental and F~ cells.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…This finding, of practical importance in interpreting results obtained with cells of various haplotype combinations, could be due to decreased efficiency of antibody binding when antigen density is reduced or to a degree of heterogeneity of gene expression among individual F~ cells. These findings differ from those obtained in the mouse, using the technique of inhibition of aggregated IgG binding by anti-Ia antisera (16), in which maximal inhibition occurred with both parental and F~ cells.…”
Section: Discussioncontrasting
confidence: 55%
“…Rabbit antirat IgG inhibited EA rosette formation, but this effect was not strain specific. Blocking of FITC-IgG aggregate binding (16) was also produced by HIS and PAS. SAS was devoid of any blocking activity.…”
Section: In Vitro Studiesmentioning
confidence: 99%
“…The previous experiment indicated that H-2-associated antigens were not in close proximity to the region of the antigen-binding (Ig) determinants on B cells . The question therefore arose whether other sites, such as the Fc receptors, were more closely linked to H-2 determinants since a role for the Fc receptor had been postulated in the regulation of B-cell activity (3,7). Spleen cells from CBA/H/WEHI (H-2k) mice were incubated with anti-H-2 serum directed against H-2k or H-2b determinants, washed, and then labeled with anti-FyG "5I-labeled FyG in the standard manner.…”
Section: Effect Of Pretreatment Withmentioning
confidence: 99%
“…In the first method, specific ligand (usually antibody) is bound to molecule A and the ability to serologically detect molecule B is subsequently evaluated. Using this method, interactions have been reported between Ia antigens and Fc IgG receptors (FcGR) 1 (1,2) and LyM antigens and FcGR (3) on B lymphocytes, and between Ia antigens and FcGR (4,5), H-2D b and Lyt 2.2 (6, 7), H-2K b and Lyt 1.2 (6, 7), H-Y and TL (8), D b and TL (6,7), and H-Y and D b (8) on T lymphocytes. The simplest (but not the only) interpretation of these data is that the interacting molecules are specifically (nonrandomly) located in close proximity to each other on the lymphocyte surface membrane.…”
mentioning
confidence: 99%